2016
DOI: 10.1001/jamaoncol.2015.6113
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pathologic Complete Response to Neoadjuvant Therapy in HER2-Positive Breast Cancer With Long-Term Outcomes

Abstract: Pathologic complete response in HER2-positive breast cancer is associated with substantially longer times to recurrence and death. This relationship is maintained in RCTs. For any particular new therapy the relationship between pCR and survival may differ. Quantifying the importance of pCR is necessary for designing efficient clinical trials, which should adapt to the relationship between pCR and survival for the therapy under investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
200
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 277 publications
(214 citation statements)
references
References 58 publications
8
200
0
6
Order By: Relevance
“…In all patients, this analysis suggested that patients who achieved pCR However, the analysis was unable to demonstrate a relationship between the effect of treatment on pCR (estimated using an odds ratio) and the effect of treatment on EFS and OS (estimated using a hazard ratio) at the study level. These findings are generally consistent with other similar studies [11,12]. The ERG accepts that there is evidence at the patient-level that a pCR responder is associated with a lower risk of EFS and OS.…”
Section: Limitations Of the Rctssupporting
confidence: 91%
“…In all patients, this analysis suggested that patients who achieved pCR However, the analysis was unable to demonstrate a relationship between the effect of treatment on pCR (estimated using an odds ratio) and the effect of treatment on EFS and OS (estimated using a hazard ratio) at the study level. These findings are generally consistent with other similar studies [11,12]. The ERG accepts that there is evidence at the patient-level that a pCR responder is associated with a lower risk of EFS and OS.…”
Section: Limitations Of the Rctssupporting
confidence: 91%
“…Finally, we obtained data for leukemia-free survival (LFS), overall survival (OS), and cumulative incidence of relapse (CIR) and non-relapse mortality (NRM) from the date of HCT. We used a hierarchical approach 14 to compare outcomes of MRD pos and MRD neg subjects: (i) when available, we used observed hazard ratios (HRs) and confidence intervals (CIs); (ii) when Kaplan-Meier curves were provided, we used Enguage Digitizer version 4.1 to calculate HRs and CIs based on an established algorithm, 15 and (iii) for articles providing survival data at single time points, we estimated HRs based on exponential decay.…”
Section: Methodsmentioning
confidence: 99%
“…The reported rates of trastuzumab use were also slightly higher than published rates, although many patients were unsure and likely did not receive trastuzumab 18 . Also, women with her2-positive disease might be more likely to receive chemotherapy and might therefore have been overrepresented in this sample of patients 19 .…”
Section: Discussionmentioning
confidence: 99%